Efficacy and safety of oral high‐trough level tacrolimus in acute/subacute interstitial pneumonia with dermatomyositis. (5th November 2018) - Suzuka, Takayasu; Kotani, Takuya; Takeuchi, Tohru; Fujiki, Youhei; Hata, Kenichiro; Yoshida, Shuzo; Shoda, Takeshi; Makino, Shigeki; Arawaka, Shigeki
Abstract: Objectives: We assessed the efficacy and safety of combination therapy with glucocorticoids and high‐trough level tacrolimus (TAC) for the treatment of acute/subacute interstitial pneumonia (A/SIP) in patients with dermatomyositis (DM). Methods: Eleven DM‐A/SIP patients were enrolled. The combination therapy with glucocorticoids and TAC was started as early as possible after DM‐A/SIP was diagnosed. We monitored the trough concentration of TAC. In the initial 3 months, we maintained the trough concentration of TAC at relatively high levels within a range of 15‐20 ng/mL. Then, we decreased the TAC doses stepwise to keep the trough concentration at 10‐15 ng/mL in the next 3 months and 5‐10 ng/mL as a maintenance dose. Results: Seven patients had clinically amyopathic DM. Six patients were positive for anti‐aminoacyl‐tRNA synthetase antibody and two were positive for anti‐melanoma differentiation‐associated gene 5 antibody. Ten patients survived for the period of the 24‐week follow up. One patient died under a tentative diagnosis of viral encephalitis at 4 months after the treatment. In the 10 surviving patients, interstitial pneumonia improved in eight patients and was not worse in two patients. Clinical examinations, including the Krebs von den Lungen‐6 levels, % forced vital capacity, and chest computed tomography score, were significantly improved by this combination therapy. Although grade 1 and 2 renal damage occurred in 4 and 2 patients, respectively. Conclusions: The present findings suggest that early therapeutic intervention by a combination with glucocorticoids and initial high‐trough level TAC is effective for DM‐A/SIP although consideration of the risks of infection and renal damage is required.